(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The development of new fluorescent reagents for determination of trace amounts of zinc in biological samples is an actual issue. Efficient reagents should characterized by high hydrophobicity, low sensitivity to media acidity and intense fluorescence in the long-wavelength region of the spectrum. Therefore, the using of a rigid π-conjugated molecule of 3-(2-pyridyl)-5-(2-hydroxyphenyl)-1,2,4-triazole as a fluorescent probe for the determination of zinc micro-quantities in biological samples is considered as a rational choice. 3-(2-pyridyl)-5-(2-hydroxyphenyl)-1,2,4-triazole is a highly hydrophobic ligand (logP=3.0±0.1). Dissociation of the protonated nitrogen atom in the pyridine cycle of the ligand occurs at pH = 4, рКа1= 3.98±0.05. The pKa2 value is equal to 8.74 ± 0.03 and corresponds to the dissociation of the N-H group of the triazole fragment. The absorption spectrum of the ligand solution in DMSO is characterized by two bands with maximum at 272 nm and 320 nm due to intraligand π-π * transitions. The values of the molar absorption coefficient for these bands are 1.18·104 l ·mol-1·cm-1 and 1.36·104 l·mol-1·cm-1, respectively. Two bands at 402 nm and 535 nm are also observed on the fluorescence spectra of the ligand. The high fluorescence intensity in the long-wavelength region of the spectrum indicates the promising use of this ligand as an analytical reagent at a creation of new fluoresce techniques. 3-(2-pyridyl)-5-(2-hydroxyphenyl)-1,2,4-triazole as chelating ligand can form two complex compounds in DMSO solution with composition ML and ML2. Complex formation is accompanied by the appearance of a third absorption band in the visible regions of the spectrum at 440 nm (ε440≈ 6,5·103 l ·mol-1·cm-1) due to LMCT transitions. In addition, the complex formation leads to fluorescence quenching. Developed fluorescent techniques for determination of zinc quantities in a sample of hair and in a tablet of vitamins "Duovit" are characterized by satisfactory precision and accuracy. The range of zinc concentrations determining in the hair sample is 71–286 μg/g, Sr=0,033 (n=3, P=0.95). The zinc content that was found in the "Duovit" tablet is well correlated with the declared content. This indicates the good selectivity of ligand in relation to the accompanying microelements.